Tumor‐derived exosomes elicit tumor suppression in murine hepatocellular carcinoma models and humans in vitro - Quan Rao; Bingfeng Zuo; Zhen Lu; Xianjun Gao; A‐Bin You; Chenxuan Wu; Du Zhi; HaiFang Yin (2016)
Hepatocellular carcinoma (HCC) remains a global challenge due to high morbidity and mortality rates and poor response to treatment. Immunotherapy, based on introduction of dendritic cells (DCs) activated by tumor cell lysates as antigens ex vivo , shows limited response rates in HCC patients. Here, we demonstrate that tumor cell–derived exosomes (TEXs), displaying an array of HCC antigens, can elicit a stronger immune response than cell lysates in vitro and in vivo . Significant tumor growth inhibition was achieved in ectopic and orthotopic HCC mice treated with TEX‐pulsed DCs. Importantly, the tumor immune microenvironment was significantly improved in orthotopic HCC mice treated by TEX‐pulsed DCs, demonstrated by increased numbers of T lymphocytes, elevated levels of interferon‐γ, and decreased levels of interleukin‐10 and tumor growth factor‐β in tumor sites. As expected, T cells played an essential role in the TEX‐pulsed DC‐mediated immune response. Notably, exosomes from HCC cells not only promoted HCC‐specific cytolysis but also provided cross‐protective effects against pancreatic cancer cells. Moreover, HCC‐specific cytolysis, elicited by DCs pulsed with human HepG2 cell–derived exosomes, was observed across different human HCC cells irrespective of human leukocyte antigen types. Conclusion : HCC TEXs can potently carry HCC antigens, trigger a strong DC‐mediated immune response, and improve the HCC tumor microenvironment. (H epatology 2016;64:456‐472)